Setetes Bakti untuk Negeri: Menggerakkan Kepedulian Masyarakat di Desa Cepokomulyo, Kecamatan Gemuh, Kabupaten Kendal melalui Aksi Donor Darah - Rosidin, Rosidin; Aprilian, Ferry Aji; Rochmatassaadah, Elliyya; Firmansyah, Achlan Abi Putra; Zakiyah, Lulu Afidati; Miladianur, Miladianur; Marzuqoh, Tarisna; A'la, Ta'rizul; Oktavian, Dani; Widianti, Kistia; Zavilia, Nila Dewi; Hidayah, Nur; Imaduddin, M Aqib (Jurnal Pengabdian Kepada Masyarakat, 2026)
Kuliah Kerja Nyata (KKN), or Student Community Service, serves as a student advocacy instrument to facilitate social transformation at the village level. This article aims to document the implementation of a blood donation drive as a flagship program conducted in Cepokomulyo Village. The primary issue identified at the site was low community participation in medical humanitarian activities due to limited access to information and psychological stigmas regarding medical procedures. This community service project employed a Community-Based Research (CBR) approach, utilizing observation and in-depth interviews for data collection. Data were analyzed using a qualitative descriptive method to identify shifts in community perception and evaluate program effectiveness. The results demonstrate a significant increase in the community's social awareness index, highlighted by achieving a blood bag collection target of 85% from the total registrants who passed medical screening. This program not only succeeded in providing blood supplies for the Indonesian Red Cross (PMI) but also reinforced the values of gotong royong (mutual cooperation) and health awareness as a tangible impact of student service in Cepokomulyo Village.